Firefly night - Waldo, Steph (Waldo, Steph. Tiny tales., 2024)
"It's hard to see in the dark ... unless you're Firefly! Will Firefly be able to show their friends the beautiful moonflower? Or will sleep win the night?"--Provided by publisher